HA Filler Injection and Skin Quality–Literature Minireview and Injection Techniques - Peng, Jui-Hui; Peng, Peter Hsien-Li (Indian Journal of Plastic Surgery, 2020)
Aging of the face produces many changes in the structure and integrity of the skin and other anatomical aspects, the three major signs of which are volume loss, sagginess, and skin quality change. Through surgical or nonsurgical procedures, it is possible to slow or even reverse these mechanisms through artificial means, including thread lifting, radiofrequency, or filler injection. Filler injections are particularly popular in recent years, owing to their convenience, efficacy, and long-lasting results. In this minireview, the author outlines the basic mechanisms behind facial aging, discusses current literature on each aspect of facial aging, and offers injection protocol recommendations based on past literature and clinical experience.
Keywords: static wrinkles; radial cheek lines; skin quality; HA filler injection; skin rejuvenation